Land Use Planning for Disaster-Prone Areas in Southern Region of Mount Merapi - Budiyanto, Gunawan (AGRIVITA, Journal of Agricultural Science, 2021)
The eruption of Mount Merapi in 2010 caused the decline of land quality and changed the land use pattern in the southern regions. This study evaluated and determined the land use planning in disaster-prone areas affected by the Mount Merapi eruption. This research was conducted from August 2018 to March 2019 in Kepuharjo village, Cangkringan, Sleman, Special Region of Yogyakarta. This study was performed by using observational methods through data collection, such as physiographic areas, volcanic materials depth, rock distribution, and soil characteristics. Prone zoning and area planning was determined using a descriptive-spatial method to produce an appropriate model for the new land use. The results revealed the difference in land suitability in the distance interval of 8 km from the mountain peak. A region located less than 8 km from the peak was predicted to be suitable for the community forest and fodder grass cultivation and could function as a conservation area. In contrast, the region located within ≥ 8 km was found to be suitable for dry land farming of food crops using alley cropping systems. Additionally, an integrated sustainable farming system should be promoted and implemented for increasing the sustainability of soil and crop productivity